FORMULASI DAN EVALUASI HANDBODY LOTION EKSTRAK DAUN BAYAM MERAH (Amaranthus tricolor L.) DENGAN VARIASI KONSENTRASI TRIETANOLAMIN DAN ASAM STEARAT SEBAGAI EMULGATOR - Yahya Febrianto; Novia Putri Santari; Wahyu Setiyaningsih (LPPM Sekolah Tinggi Ilmu Farmasi Nusaputera, 2021)
Red spinach leaves contain flavonoids, saponins and tannins which have antioxidant potential which can be formulated into Handbody lotion. Handbody lotion is a cosmetic preparation used on the hands and body, formed from a liquid emulsion consisting of an oil phase and a water phase which is stabilized by the emulgator. The purpose of this study was to determine the effect of triethanolamine and stearic acid concentrations as emulsifiers and to determine the comparison of variations in the concentrations of triethanolamine and stearic acid which meet the physical evaluation requirements of handbody lotion preparations. The research method used is experimental research with data analysis using one way ANOVA. The results showed that the red spinach leaf extract handbody lotion was homogeneous and had a pink color, semi-solid shape and a distinctive smell of strawberry. It has a pH range of 7.30-7.42, a range of values for the spreadability of 5.20-6.17 cm, a range of values for adhesion from 4.42-6.27 seconds. The concentrations of triethanolamine and stearic acid as emulgators had a significant effect on the physical evaluation of the red spinach leaf extract handbody lotion including the pH test, spreadability and adhesion with a significance of p> 0.05. The comparison of the formula variation triethanolamine emulgator: stearic acid that meets the test requirements is formula 1 (2%: 7%), formula 2 (2.5%: 6.5%), formula 3 (3%: 6%), formula 4 ( 3.5%: 5.5%), formula 5 (4%: 5%).